Impact of a patient and family participation education program on hospital nurses' attitudes and competencies: A controlled before-after study - Peter van Oort; Jolanda Maaskant; Marie Louise Luttik; Anne Eskes (Elsevier, 2024)
Objective: We designed a Patient and Family Participation Education Program (PFEP) with the aim of fostering a positive attitude and enhancing the competencies of hospital nurses required for effective patient and family participation in care. Methods: In a Dutch university hospital, we conducted a before-after study. The PFEP comprising three courses: family conversation, supporting shared decision-making, and health literacy. We assessed nursing attitudes using the FINC-NA questionnaire and competencies with a separate questionnaire before and three months after the program. Changes in attitudes and competencies were analyzed using regression analysis. Results: Twenty-two nurses participated in the education group, and 58 participated as controls.After three months, the change scores for the education group were statistically significantly higher on the total attitude score (FINC-NA) compared to the control group. Moreover, in six out of twelve competencies, the education group demonstrated significantly higher scores than the control group. Conclusion: The educational program appeared effective in promoting nurses' attitudes and feelings of competencies towards patient and family-centered care. Innovation: A blended education program focusing on patient and family has potential value for implementation in hospital care settings, especially for hospitals aiming to cultivate a more patient- and family-centered environment.